Locating Creativity in Differing Approaches to Musical Robotics - Kemper, Steven (Frontiers in Robotics and AI, 2021)
The field of musical robotics presents an interesting case study of the intersection between creativity and robotics. While the potential for machines to express creativity represents an important issue in the field of robotics and AI, this subject is especially relevant in the case of machines that replicate human activities that are traditionally associated with creativity, such as music making. There are several different approaches that fall under the broad category of musical robotics, and creativity is expressed differently based on the design and goals of each approach. By exploring elements of design, capacity for sonic nuance, control, and musical output, this article evaluates the locus of creativity in six of the most prominent approaches to musical robots, including: (1) nonspecialized anthropomorphic robots that can play musical instruments, (2) specialized anthropomorphic robots that model the physical actions of human musicians, (3) semi-anthropomorphic robotic musicians, (4) non-anthropomorphic robotic instruments, (5) cooperative musical robots, and (6) individual actuators used for their own sound production capabilities.